Psychrometrics For Shah Alam / Abdul Razak Yaacob and Wan Anyie Jok - Yaacob, Abdul Razak; Jok, Wan Anyie (Faculty of Mechanical Engineering, 1995)
Air is a mechanical mixture of gases and water vapor. Dry air is composed chiefly of nitrogen, oxygen and carbon dioxide. With regard to these dry air compounds, the composition of the air is practically the same everywhere. On the other hand the amount of water vapor in the air varies greatly with the particular locality and with the weather conditions. The science which investigates the thermal properties of moist air, measurement and control of the moisture contents of air may properly be termed psychrometrics. Psychromertrics charts are graphical presentations of the psychrometric properties of the air. The use of such chart permits the graphical analysis of psychrometric data and processes, and thereby facilitates the solution of many practical problems dealing with air. Since there are no psychrometric charts available in the form of computer display done by any invidual or organisation in Malaysia, in this project, a psychrometric chart is developed and used to analyse the properties of air in Shah Alam and compared it with certain places in Malaysia. This developed